Improving the Professional Competence of Religious College Lecturers: Challenges and Strategies - Urbanus Sukri (Pengertian: Jurnal Pendidikan Indonesia (PJPI), 2026)
Improving the professional competence of lecturers in religious universities, which is a key factor in improving the quality of education, faces various challenges both internally, such as limited resources for professional development, high administrative burdens, and limited access to appropriate technology and training, and externally, including government policies that do not fully support lecturer development and rapid curriculum changes that require lecturers to continue to adapt, thus requiring a development strategy that includes technology-based training programs, improving supporting facilities such as lecturer development centers, and increasing collaboration between religious universities and other educational institutions both domestically and abroad, as well as implementing an academic culture that encourages innovation and collaboration between lecturers to improve the quality of education and the graduates produced.